2021
DOI: 10.18502/ijph.v50i5.6106
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Group B Streptococcus in Vagina and Rectum of Pregnant Women of Islamic & Non-Islamic Countries: A Systematic Review and Meta-Analysis

Abstract: Background: Group B streptococcus or streptococcus Agalactia is a gram positive beta hemolytic bacteria which is the main factor in neonatal infections. This study aimed at determining the prevalence of GBS in world and clarifying the rate of this infection in Islamic and non-Islamic countries. Methods: We performed a systematic search by using different databases including Medline, Scopus, Science Direct, Psycho-Info ProQuest and Web of Science published up to Feb 2019. We undertook meta-analysis to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…In contrast, as shown in Table 3, the pooled prevalence is much lower in Asia. A prevalence 11.1% in South East Asia, 65 12.9% in Asia 67 and 10% in China 66 . We found a prevalence of 11.8% for Asia, which included countries from East, South and West Asia concurring with findings from previous reviews.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, as shown in Table 3, the pooled prevalence is much lower in Asia. A prevalence 11.1% in South East Asia, 65 12.9% in Asia 67 and 10% in China 66 . We found a prevalence of 11.8% for Asia, which included countries from East, South and West Asia concurring with findings from previous reviews.…”
Section: Discussionsupporting
confidence: 90%
“…We found a prevalence of 11.8% for Asia, which included countries from East, South and West Asia concurring with findings from previous reviews. Data from the Americas and Europe demonstrate a pooled prevalence that is intermediate; in the Americas, it ranged from 18.6% 67 to 19.7% 65 ; in Europe, from 16.4% 67 to 19.0% 65 . Results from our analysis show a similar trend; the pooled prevalence is 22.6% for the Americas and 19.7% for Europe.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The prevalence of maternal GBS colonization in studies that reported samples from pregnant women before 35 weeks of pregnancy was 17% (95% CI, 15–18%), then 15% (95% CI, 13–16%) in those sampled after 35 weeks and 14% (95% CI, 13–16%) at the moment of delivery [ 2 ]. Another systematic review conducted by Abbasalizadeh F. et al included 245 full texts that reported the prevalence of GBS colonization in pregnant women from all the studied countries was 15.5% (95% CI, 14.2–17%) [ 36 ]. Similar results were obtained in the present study, where the prevalence of colonized pregnant women included in the study was 17.3%.…”
Section: Discussionmentioning
confidence: 99%
“… 32 The pooled estimated prevalence of Group B Streptococcus in the vagina and rectum of pregnant women in Islamic and non-Islamic countries was 15% and 14%, respectively, according to a meta-analysis and systemic review. 33 Standards and laboratory diagnostic methods, differences in study location, differences in respondents’ residence, differences in previous obstetric history, bacteriological method for organism detection, statistical differences in the study population, laboratory staff skill, and health and medical policies of countries and geographic regions could all contribute to the disparity.…”
Section: Discussionmentioning
confidence: 99%